Impact of Lewy bodies disease on visual skills and memory abilities: from prodromal stages to dementia - Bussè, Cinzia; Mitolo, Micaela; Mozzetta, Stefano; Venneri, Annalena; Cagnin, Annachiara (Frontiers in Psychiatry, 2024)
Dementia with Lewy bodies (DLB) and its prodromal presentation with mild cognitive impairment is characterized by prominent deficits in attention/executive domains and in visual processing abilities with relative sparing of memory. Neuropsychological research is continuously refining the tools to define more in detail the patterns of relatively preserved and impaired cognitive abilities that help differential diagnosis between DLB and Alzheimer disease (AD). This review summarizes the main studies exploring specific cognitive tasks investigating different visual processing abilities and verbal memory that better differentiate DLB from AD. The findings provide evidence that substantial impairments in visual-spatial and visual-constructional abilities and relatively better performance on memory tasks that depend on hippocampal function characterize the prodromal stage of DLB. The ability to detect early indicators of prodromal DLB through clinical and cognitive assessments is the first step to guide instrumental diagnostic work-ups and provide the opportunity for early intervention.